Implementation of the Weighted Product Method to Determine Scholarship Recipients - Putu Eka Parianthana; I Wayan Adi Sparta; Ayu Gde Chrisna Udayanie (Yayasan Sinergi Widya Nusantara (Sidyanusa), 2025)
This study aims to help address the problems that occur at SMAN 2 KUTA SELATAN in determining the selection of scholarship recipients based on economics. In its Decision Support System (DSS) We use the Weighted Product (WP) method, by determining the criteria needed to be used in determining the best alternative by multiplying the normalized criteria values, where each criterion value is raised to the power of a predetermined weight. The results of this study show which students are more deserving or should receive scholarship assistance, However, due to the large amount of data that must be collected, the division of the criteria must be carefully twisted in such a way as to produce effectiveness in its determination. Despite the constraints, in fact this method is quite effective in determining system-based scholarship selection decisions, the school has no difficulty in making the selection because the WP method makes it easier for them and only takes a little time.